Formulation, In Vitro Release, and Dermal Irritation Evaluation of Celecoxib Nanoemulsions Using Clove and Nutmeg Oils - Ayu Shabrina (Universitas Wahid Hasyim Semarang, 2025)
Celecoxib is a selective cyclooxygenase-2 inhibitor widely used for inflammatory conditions; however, its oral administration is associated with gastrointestinal adverse effects, particularly during long-term therapy. Topical delivery using nanoemulsion systems represents a promising alternative to enhance dermal penetration while minimizing systemic side effects. The selection of carrier oil plays a crucial role in determining the physicochemical characteristics, drug release behavior, and skin safety of nanoemulsion formulations.This study aimed to formulate celecoxib nanoemulsions using clove oil and nutmeg oil as carrier oils and to evaluate their physicochemical properties, in vitro drug release profiles, and dermal irritation potential. Celecoxib nanoemulsions were prepared using Tween 80 and polyethylene glycol 400 as surfactant and cosurfactant, with varying concentrations (3%, 6%, and 12%) of clove oil or nutmeg oil. The formulations were evaluated for organoleptic properties, homogeneity, percent transmittance, pH, particle size, and polydispersity index. In vitro drug release was assessed using a Franz diffusion cell with phosphate buffer pH 7.4 as the receptor medium. Dermal irritation was evaluated in New Zealand White rabbits using the primary irritation index method. Results: All nanoemulsion formulations exhibited clear, transparent appearances with nanoscale droplet sizes and acceptable polydispersity indices, indicating uniform particle distribution. The pH values were within the suitable range for topical application. In vitro release studies demonstrated sustained celecoxib release profiles, with no significant differences observed between formulations containing clove oil and nutmeg oil. Dermal irritation testing showed no signs of erythema or edema, resulting in a primary irritation index of zero for all formulations.Celecoxib nanoemulsions formulated with clove oil or nutmeg oil as carrier oils demonstrated favorable physicochemical characteristics, satisfactory drug release behavior, and excellent dermal safety, highlighting their potential as non-irritating topical delivery systems for anti-inflammatory therapy.